OMONKHONA IN BOYSUN DISTRICT OF SURKHANDARYA REGION TOURISM-HEALING SHELTER (Academicia Globe: Inderscience Research, 2023)
Information on the development of recreational systems in Boysun district of Surhandarya region in this article quoted.